Safety and Efficacy of Novel Cost-Effective EUS Coiling and Glue Technique for the Management of Large Gastric Varices: A Long-Term Follow-up Study - Khare, Shivam; Arora, Anil; Varghese, Jijo; Singla, Vikas; Rahman, Asif; Kumar, Ashish; Ranjan, Piyush; Kumar, Mandhir; Sharma, Praveen; Bansal, Naresh; Anikhindi, Shrihari; Sachdeva, Munish; Khandelwal, Asheish; Gupta, Mayank; Giri, Suprabhat (Journal of Digestive Endoscopy, 2024)
Aims and Objective Mortality by gastric variceal bleeding can reach up to 30%. Gastric varices can be treated by either direct endoscopic glue or endoscopic ultrasound (EUS) coiling + glue injection. Now, enough data show that EUS coil + glue is an effective option for large varices. However, it is a costlier option than direct endoscopic glue injection. In our study, after putting the coil under EUS guidance, direct endoscopic glue injection is done with a 21G sclerotherapy needle. Since the EUS needle was not used for the glue injection, it can be reused for up to three cases for deployment of the EUS coil, hence reducing the cost of the whole procedure. In short, our study aims to find the safety and efficacy of a cost-effective method of EUS coiling + glue injection in a cohort of the Indian population.Material and Methods Retrospective review of prospectively collected data on EUS coiling + direct endoscopic glue injection over a period spanning from July 2017 to December 2023 from a tertiary care center in North India.Results A total of 103 patients (gastroesophageal varices type 2, GOV2 [n = 82] and isolated gastric varices type 1, IGV1 [n = 21]) were taken up for the study. Among the 103 patients, 74 patients were males and 29 were females. The mean follow-up duration of the study population was 34.2 ± 21 months. The average size of the varix was 2.3 cm. The average number of coils was 3.3 and the volume of injected glue was 3.1 mL. In our study, 4 out of 103 patients had rebleeding, but the cause of rebleeding turned out to be nonvariceal. Regarding the intraprocedural and postprocedural adverse events, 1 out of 103 patients in our study experienced abdominal pain and fever, which responded to oral analgesics and antipyretics. There was no active bleeding from the puncture site or evidence of systemic embolization. Technical success was 100% in our study. Reuse of needles was not associated with any increment in risk of infection.Conclusion EUS coiling + direct endoscopic glue injection is a safe and effective endoscopic therapy for large gastric varices with sustainable long-term beneficial effects with a negligible amount of rebleeding. Direct endoscopic injection of glue following EUS coiling with a 21G sclerotherapy needle can significantly reduce the cost of the procedure without any risk of infection.
Keywords: EUS coil; gastric varices; rebleeding